2022
DOI: 10.1186/s42269-022-00938-2
|View full text |Cite
|
Sign up to set email alerts
|

Arterial tortuosity syndrome (variants in SLC2A10 gene) in two pediatric patients in the same city of Spain: a case report

Abstract: Background Arterial tortuosity syndrome (ATS) (OMIM #208050) is a very rare autosomal recessive connective tissue disease characterized by elongation, tortuosity, and predisposition of aneurysms formation in medium and large-caliber arteries, vascular dissection, and ischemic events. To date, approximately 100 patients have been reported carrying some of the fewer than 35 causal mutations in the SLC2A10 gene. Case presentation Here we present the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Beyens et al have reported a male-to-female ratio of 27:22 in a retrospective characterization of 50 ATS patients’ symptoms [ 2 ]. The ATS typically appears during the early years of life, depending on complications that occur in infancy and the participation of several systems affected by this recessively inherited disorder [ 2 , 4 ]. From the analysis of a cohort of 50 new ATS patients and reviewing the 52 previously reported ATS patients’ data, the age at diagnosis for this disease was found to be 4.84 years (mean) and two years (median) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyens et al have reported a male-to-female ratio of 27:22 in a retrospective characterization of 50 ATS patients’ symptoms [ 2 ]. The ATS typically appears during the early years of life, depending on complications that occur in infancy and the participation of several systems affected by this recessively inherited disorder [ 2 , 4 ]. From the analysis of a cohort of 50 new ATS patients and reviewing the 52 previously reported ATS patients’ data, the age at diagnosis for this disease was found to be 4.84 years (mean) and two years (median) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arterial tortuosity syndrome (ATS) is a rare connective tissue disorder characterized by abnormal twists and turns (tortuosity) of the arteries. The condition was first reported around 55 years ago and is inherited in an autosomal recessive manner [ 1 , 2 ]. It affects both males and females, with no significant gender bias [ 3 ].…”
Section: Introductionmentioning
confidence: 99%